A SSZ-13 zeolite catalyst and its preparation method and application
By using urea instead of trimethyldamantamantamide in the preparation of SSZ-13 zeolite catalyst, the problem of high preparation cost is solved, and high yield and low cost preparation is achieved. The catalyst has excellent catalytic properties and anti-deactivation properties.
Patent Information
- Application Number
- CN202310537814.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-12
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-05-12
AI Technical Summary
The existing SSZ-13 zeolite catalyst is costly to prepare, mainly because the commonly used template agent trimethylamantamide is expensive and has low yields, which hinders its industrial application.
Urea is used to replace part of trimethylamantamantamide. By controlling the molar ratio of urea in the preparation raw materials, the amount of trimethylamantamantamide is reduced, and the yield of SSZ-13 zeolite catalyst is increased, thereby reducing the preparation cost.
The preparation cost of SSZ-13 zeolite catalyst is effectively reduced, and the yield of the catalyst is improved. The catalyst has a CHA topology, small grains, high crystallinity, high silicon-aluminum ratio, and excellent catalytic and anti-deactivation properties.
Smart Images

Figure CN116571270B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an SSZ-13 zeolite catalyst and a preparation method and application thereof, belonging to the technical field of catalyst preparation. Background Art
[0002] my country's energy structure is characterized by rich coal, poor oil and little gas. Due to the scarcity of oil resources, the commonly used naphtha cracking technology to produce olefins in foreign countries is restricted in my country, resulting in a huge market gap in domestic olefins. Methanol to olefins (MTO) technology can convert my country's large reserves of coal and other non-oil resources into important chemical raw materials such as olefins, which can reduce my country's dependence on oil and has great strategic significance.
[0003] The core of MTO is the development of catalyst system. There are many catalysts that can be used for MTO. The current research focus is mainly on octahedral small pore zeolites. Among them, SAPO-34 molecular sieve with CHA topology has become the best MTO catalyst today due to its special pore structure, weak acid center and high selectivity for low-carbon olefins. At present, the synthesis and performance research of SAPO-34 has become mature. Compared with SAPO-34 molecular sieve, SSZ-13 zeolite also has CHA topology and has low carbon selectivity. In addition, SSZ-13 zeolite does not need to consider the problems of phosphorus pollution of waste catalysts. Because of its strong acidity, its reaction temperature can be greatly reduced, thereby reducing energy consumption and can be used as an MTO catalyst. However, the template agent trimethylammonium adamantane (TMAdaOH) commonly used to prepare SSZ-13 zeolite catalyst is extremely expensive, and the yield of SSZ-13 zeolite catalyst prepared by conventional methods is low, which makes the preparation cost high and hinders its industrial application.
[0004] Therefore, reducing the preparation cost of SSZ-13 zeolite catalyst is of great practical significance and can provide important theoretical basis and support for the industrial application of SSZ-13 zeolite catalyst. Summary of the invention
[0005] In view of the above problems, the present invention provides a method for preparing a SSZ-13 zeolite catalyst, which uses urea to replace part of trimethyladamantanamine, thereby reducing the amount of trimethyladamantanamine used in the preparation process, improving the yield of the SSZ-13 zeolite catalyst, and effectively reducing the preparation cost.
[0006] The present invention also provides a SSZ-13 zeolite catalyst, which is prepared by the above preparation method. The catalyst has a CHA topological structure, no impurity crystals, a silicon-aluminum ratio of 10-100, and a micropore volume of 0.15-0.35 cm 3 / g, specific surface area is 300-700m 2 / g, the average grain size is 100nm-1μm, and it has the characteristics of small grains, high crystallinity and high silicon-aluminum ratio.
[0007] The present invention also provides a method for preparing olefins from methanol, which adopts the above SSZ-13 zeolite catalyst and has higher methanol conversion rate and olefin selectivity.
[0008] The present invention provides a method for preparing a SSZ-13 zeolite catalyst, comprising the following steps:
[0009] 1) mixing a template, sodium hydroxide and deionized water to obtain a mixed solution;
[0010] 2) adding an aluminum source to the mixed solution, and then adding a silicon source and a seed crystal to obtain a mixed gel;
[0011] 3) performing crystallization treatment and post-treatment on the mixed gel in sequence to obtain Na-SSZ-13 zeolite;
[0012] 4) sequentially subjecting the Na-SSZ-13 zeolite to ion exchange, drying, and calcination to obtain the SSZ-13 zeolite catalyst;
[0013] The template comprises trimethylammonium adamantane and urea; the molar ratio of the trimethylammonium adamantane, urea, sodium hydroxide, aluminum source, silicon source and deionized water is (1-20): (1-10): (5-15): (0.5-5): (50-100): (500-4000).
[0014] According to one embodiment of the present invention, the molar ratio of trimethylammonium adamantane, urea, sodium hydroxide, aluminum source, silicon source and deionized water is (1-20): (2-8): (6-15): (0.5-2.5): (60-100): (1000-2000).
[0015] According to one embodiment of the present invention, the molar ratio of trimethylammonium adamantane, urea, sodium hydroxide, aluminum source, silicon source and deionized water is (5-16): (6-8): (6-13): (1-2.5): (80-100): (1200-1500).
[0016] According to one embodiment of the present invention, the aluminum source is aluminum hydroxide; and the silicon source is alkaline silica sol.
[0017] According to one embodiment of the present invention, the temperature of the crystallization treatment is 140-180° C., and the crystallization time is 12-36 hours.
[0018] According to one embodiment of the present invention, the ion exchange solution is a 1 M NH4Cl solution, and the ion exchange is performed on 1 g of the SSZ-13 zeolite per 50 mL of the NH4Cl solution.
[0019] According to one embodiment of the present invention, the ion exchange is performed three times, each time for 1-3 hours.
[0020] According to one embodiment of the present invention, the temperature of the ion exchange is 60-80°C.
[0021] The present invention also provides a SSZ-13 zeolite catalyst, which is prepared by any of the preparation methods described above, wherein the SSZ-13 zeolite catalyst has a silicon-aluminum ratio of 10-100 and a micropore volume of 0.15-0.35 cm 3 / g, specific surface area is 300-700m 2 / g, and the average grain size is 100nm-1μm.
[0022] The present invention also provides a method for preparing olefins from methanol, which adopts the above-mentioned SSZ-13 zeolite catalyst for catalysis.
[0023] In the preparation method of the present invention, relatively cheap urea is added as a template agent, and the molar ratio of urea in the preparation raw material is controlled, so that the amount of trimethylammonium adamantane used in the preparation process can be reduced, and the yield of the SSZ-13 zeolite catalyst can be increased, thereby reducing the preparation cost. The SSZ-13 zeolite catalyst obtained by the preparation method of the present invention has a CHA topological structure, no impurity crystals, a silicon-aluminum ratio of 10-100, and a micropore volume of 0.15-0.35cm 3 / g, specific surface area is 300-700m 2 / g, with an average crystal size of 100nm-1μm, small crystals, high crystallinity and high silicon-aluminum ratio. When the SSZ-13 zeolite catalyst of the present invention is used for methanol to olefins, the catalytic performance and anti-deactivation performance are relatively excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The yield change curve of SSZ-13 zeolite catalyst prepared in Comparative Example 1 and Examples 1-5;
[0025] Figure 2a is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Comparative Example 1 at a scale of 2 μm;
[0026] Figure 2a1 is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Comparative Example 1 at a scale of 1 μm;
[0027] Figure 2bis a scanning electron microscope image of the SSZ-13 zeolite catalyst in Comparative Example 2 at a scale of 2 μm;
[0028] Figure 2b1 is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Comparative Example 2 at a scale of 1 μm;
[0029] Figure 2c is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Comparative Example 3 at a scale of 2 μm;
[0030] Figure 2c1 is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Comparative Example 3 at a scale of 1 μm;
[0031] Figure 2d is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Example 1 at a scale of 2 μm;
[0032] Figure 2d1 is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Example 1 at a scale of 1 μm;
[0033] Figure 2e is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Example 2 at a scale of 2 μm;
[0034] Figure 2e1 is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Example 2 at a scale of 1 μm;
[0035] Figure 2f is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Example 3 at a scale of 2 μm;
[0036] Figure 2f1 is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Example 3 at a scale of 1 μm;
[0037] Figure 2g is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Example 4 at a scale of 2 μm;
[0038] Figure 2g1 is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Example 4 at a scale of 1 μm;
[0039] Figure 2h is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Example 5 at a scale of 2 μm;
[0040] Figure 2h1 is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Example 5 at a scale of 1 μm;
[0041] Figure 2i is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Example 6 at a scale of 2 μm;
[0042] Figure 2i1 is a scanning electron microscope image of the SSZ-13 zeolite catalyst in Example 6 at a scale of 1 μm;
[0043] Figure 3 XRD spectra of SSZ-13 zeolite catalysts prepared in Comparative Examples 1-3 and Examples 1-6;
[0044] Figure 4 The nitrogen adsorption-desorption isotherms of the SSZ-13 zeolite catalysts prepared in Comparative Example 1, Example 3 and Example 6;
[0045] Figure 5 This is a graph showing the evaluation results of the methanol to olefins reaction using the SSZ-13 zeolite catalysts prepared in Comparative Example 1, Example 3 and Example 6;
[0046] Figure 6 The olefin selectivity evaluation results of the SSZ-13 zeolite catalysts of Comparative Example 1, Example 3 and Example 6 are shown. DETAILED DESCRIPTION
[0047] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0048] The first aspect of the present invention provides a method for preparing a SSZ-13 zeolite catalyst, comprising the following steps:
[0049] 1) mixing a template, sodium hydroxide and deionized water to obtain a mixed solution;
[0050] 2) adding an aluminum source to the mixed solution, and then adding a silicon source and a seed crystal to obtain a mixed gel;
[0051] 3) performing crystallization treatment and post-treatment on the mixed gel in sequence to obtain Na-SSZ-13 zeolite;
[0052] 4) sequentially subjecting the Na-SSZ-13 zeolite to ion exchange, drying, and calcination to obtain a SSZ-13 zeolite catalyst;
[0053] The template comprises trimethylammonium adamantane and urea; the molar ratio of trimethylammonium adamantane, urea, sodium hydroxide, aluminum source, silicon source and deionized water is (1-20): (1-10): (5-15): (0.5-5): (50-100): (500-4000).
[0054] It should be explained that the above method specifically includes: the synthesis of Na-SSZ-13 zeolite and the process of ion exchange of Na-SSZ-13 zeolite.
[0055] In the above step 2), stirring is required after adding the silicon source and the seed crystal, and the stirring time is controlled to be 1-4 hours.
[0056] The post-treatment in the above step 3) includes cooling, centrifugation or filtration to neutrality, drying and calcination, wherein the drying temperature is 80-120° C. and the time is 12 hours, and the calcination temperature is 500-600° C. and the time is 6-10 hours. The calcination is to remove the template agent trimethylammonium adamantanum and urea.
[0057] The above ion exchange refers to replacing the Na in Na-SSZ-13 zeolite with specific ions. + , and further obtain the hydrogen-type SSZ-13 zeolite catalyst. Only when the Na-SSZ-13 zeolite is ion-exchanged into the H-type can it be used as a catalyst carrier to load the active components.
[0058] The molar ratio of the above-mentioned trimethyladamantanium, urea, sodium hydroxide, aluminum source, silicon source and deionized water is calculated based on TMAdaOH, Urea, Na2O, Al2O3, SiO2 and H2O.
[0059] In the above step 4), the Na-SSZ-13 zeolite is dried to remove the moisture brought by the ion exchange, and the calcination treatment is to convert the exchanged ions into hydrogen to obtain the hydrogen-type SSZ-13 zeolite catalyst.
[0060] The inventors found that adding urea can fill the cavities of the SSZ-13 zeolite catalyst. Therefore, urea can be used together with trimethyladamantanamine as a template to guide the structure of the catalyst, thereby reducing the amount of trimethyladamantanamine used. Compared with not adding urea, the amount of trimethyladamantanamine used can be reduced by 42.9%, significantly reducing the preparation cost of the SSZ-13 zeolite catalyst.
[0061] In addition, compared to only adding trimethyladamantanamine, the addition of urea can not only significantly improve the yield of the catalyst, but also the catalytic performance of the catalyst has excellent performance. The inventor has analyzed the reason and believes that it may be that urea has the effect of delaying the growth of SSZ-13 zeolite catalyst nuclei, so along with the addition of urea, it can appropriately suppress the continued growth of SSZ-13 zeolite catalyst nuclei volume and guide the generation of more nuclei, thereby improving the yield of the catalyst. And along with the generation of more nuclei, the solute distributed on each nucleus will be reduced, thereby also making the catalyst have a generation trend of small particle size, and then making the catalyst have excellent molecular diffusion performance and catalytic performance.
[0062] Of course, as the amount of urea increases, the amount of trimethylammonium adamantane will gradually decrease and the yield of the catalyst will gradually increase. However, the inventors have found that when the amount of urea exceeds a certain range, there will be a situation where crystallization is hindered, thereby causing the yield of the SSZ-13 zeolite catalyst to decrease and the catalytic performance to deteriorate. Therefore, in order to ensure that urea has a positive driving effect on the performance of the SSZ-13 zeolite catalyst, the present invention controls the molar ratio of trimethylammonium adamantane, urea, sodium hydroxide, aluminum source, silicon source and deionized water to be (1-20): (1-10): (5-15): (0.5-5): (50-100): (500-4000), so that while improving the yield and reducing the preparation cost, the catalytic performance and anti-deactivation performance of the SSZ-13 zeolite catalyst are taken into account.
[0063] According to the inventors' research, when the molar ratio of trimethylammonium adamantane, urea, sodium hydroxide, aluminum source, silicon source and deionized water is controlled to be (1-20): (2-8): (6-15): (0.5-2.5): (60-100): (1000-2000), the yield of SSZ-13 zeolite catalyst can be increased to more than 85%.
[0064] Furthermore, when the molar ratio of trimethylammonium adamantane, urea, sodium hydroxide, aluminum source, silicon source and deionized water is (5-16):(6-8):(6-13):(1-2.5):(80-100):(1200-1500), the yield of SSZ-13 zeolite catalyst can reach more than 97%, effectively reducing the preparation cost.
[0065] In a specific implementation process, the aluminum source is aluminum hydroxide; and the silicon source is alkaline silica sol.
[0066] In the present invention, the crystallization treatment temperature is 140-180°C and the crystallization time is 12-36h. When the crystallization temperature is too high and the time is too long, the energy consumption increases; and when the crystallization temperature is too low and the time is too short, incomplete crystallization will result. Therefore, limiting the crystallization treatment temperature to 140-180°C and the crystallization time to 12-36h can complete crystallization at a lower cost.
[0067] According to the inventor's research, the ion exchange solution is an NH4Cl solution, and the concentration of the NH4Cl solution is 1 M; each 50 mL of the NH4Cl solution corresponds to 1 g of Na-SSZ-13 zeolite.
[0068] After further study, the number of ion exchange is three times, and the time is 1-3 hours each time. Preferably, the time of each ion exchange is 2 hours.
[0069] In a specific implementation process, the ion exchange temperature is 60-80° C. In some embodiments, the preferred ion exchange temperature is 70° C.
[0070] The second aspect of the present invention provides a SSZ-13 zeolite catalyst prepared by any of the above methods, which has the characteristics of small crystals, high crystallinity, high silicon-aluminum ratio, and excellent molecular diffusion performance. The silicon-aluminum ratio of the SSZ-13 zeolite catalyst is 10-100, and the micropore volume is 0.15-0.35cm 3 / g, specific surface area is 300-700m 2 / g, and the average grain size is 100nm-1μm. According to the catalytic performance, the micropore volume of the catalyst is 0.31cm 3 / g, specific surface area is 640m 2 / g.
[0071] The third aspect of the present invention also provides a method for preparing olefins from methanol, wherein methanol is used as a raw material and an SSZ-13 zeolite methanol catalyst is used to prepare olefins, the catalyst life is 3-16 hours, and the olefin selectivity is 72-88%.
[0072] The present invention is described in more detail below through specific examples.
[0073] Example 1
[0074] The preparation of the SSZ-13 zeolite catalyst of the present embodiment comprises the following steps:
[0075] 1) 0.24 g of urea, 23.64 g of a 25 wt.% TMAdaOH solution, 1.2 g of sodium hydroxide and 4.68 g of deionized water were stirred and mixed to obtain a mixed solution;
[0076] 2) After adding 0.5 g of aluminum hydroxide to the mixed solution, the mixture was stirred vigorously for 10 minutes; then 40 g of silicon source (containing 30 wt.% SiO2) and 0.36 g of seed crystals were added, and the mixture was stirred vigorously for 2 h to obtain a mixed gel;
[0077] 3) The mixed gel was transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for dynamic crystallization at a crystallization temperature of 160°C for 12 hours. After the crystallization, the kettle was taken out and quenched to room temperature with water, centrifuged and washed with water until neutral. The obtained sample was dried in an oven at 120°C and then calcined in a muffle furnace at a high temperature of 550°C for 10 hours to obtain Na-SSZ-13 zeolite;
[0078] 4) The calcined sample was ion exchanged three times in 1M NH4Cl solution, the amount of NH4Cl solution was: every 50mL NH4Cl solution corresponds to 1g zeolite, the ion exchange temperature was 70°C, the ion exchange time was 2h, and the SSZ-13 zeolite catalyst was obtained after high-temperature calcination again, which was named SSZ-13-2R.
[0079] Wherein, based on TMAdaOH, Urea, Na2O, Al2O3, SiO2, and H2O, the molar ratio of trimethylammonium adamantane, urea, sodium hydroxide, aluminum source, silicon source, and deionized water is 14:2:7.5:1.6:100:1400.
[0080] Example 2
[0081] The preparation of the SSZ-13 zeolite catalyst of the present embodiment comprises the following steps:
[0082] 1) 0.48 g of urea, 23.64 g of a 25 wt.% TMAdaOH solution, 1.2 g of sodium hydroxide and 4.68 g of deionized water were stirred and mixed to obtain a mixed solution;
[0083] 2) After adding 0.5 g of aluminum hydroxide to the mixed solution, the mixture was stirred vigorously for 10 minutes; then 40 g of silicon source (containing 30 wt.% SiO2) and 0.36 g of seed crystals were added, and the mixture was stirred vigorously for 2 h to obtain a mixed gel;
[0084] 3) The mixed gel was transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for dynamic crystallization at a crystallization temperature of 160°C for 12 hours. After the crystallization, the kettle was taken out and quenched to room temperature with water, centrifuged and washed with water until neutral. The obtained sample was dried in an oven at 120°C and then calcined in a muffle furnace at a high temperature of 550°C for 10 hours to obtain Na-SSZ-13 zeolite;
[0085] 4) The calcined sample was ion exchanged three times in 1M NH4Cl solution, the amount of NH4Cl solution was: every 50mL NH4Cl solution corresponds to 1g zeolite, the ion exchange temperature was 70°C, the ion exchange time was 2h, and the SSZ-13 zeolite catalyst was obtained after high-temperature calcination again, which was named SSZ-13-4R.
[0086] Wherein, based on TMAdaOH, Urea, Na2O, Al2O3, SiO2, and H2O, the molar ratio of trimethylammonium adamantanum, urea, sodium hydroxide, aluminum source, silicon source, and deionized water is 14:4:7.5:1.6:100:1400.
[0087] Example 3
[0088] The preparation of the SSZ-13 zeolite catalyst of the present embodiment comprises the following steps:
[0089] 1) 0.73 g of urea, 23.64 g of a 25 wt.% TMAdaOH solution, 1.2 g of sodium hydroxide and 4.68 g of deionized water were stirred and mixed to obtain a mixed solution;
[0090] 2) After adding 0.5 g of aluminum hydroxide to the mixed solution, the mixture was stirred vigorously for 10 minutes; then 40 g of silicon source (containing 30 wt.% SiO2) and 0.36 g of seed crystals were added, and the mixture was stirred vigorously for 2 h to obtain a mixed gel;
[0091] 3) The mixed gel was transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for dynamic crystallization at a crystallization temperature of 160°C for 12 hours. After the crystallization, the kettle was taken out and quenched to room temperature with water, centrifuged and washed with water until neutral. The obtained sample was dried in an oven at 120°C and then calcined in a muffle furnace at a high temperature of 550°C for 10 hours to obtain Na-SSZ-13 zeolite;
[0092] 4) The calcined sample was ion exchanged three times in 1M NH4Cl solution, the amount of NH4Cl solution was: every 50mL NH4Cl solution corresponds to 1g zeolite, the ion exchange temperature was 70°C, the ion exchange time was 2h, and the SSZ-13 zeolite catalyst was obtained after high-temperature calcination again, which was named SSZ-13-6R.
[0093] Wherein, based on TMAdaOH, Urea, Na2O, Al2O3, SiO2, and H2O, the molar ratio of trimethylammonium adamantanum, urea, sodium hydroxide, aluminum source, silicon source, and deionized water is 14:6:7.5:1.6:100:1400.
[0094] Example 4
[0095] The preparation of the SSZ-13 zeolite catalyst of the present embodiment comprises the following steps:
[0096] 1) 0.97 g of urea, 23.64 g of a 25 wt.% TMAdaOH solution, 1.2 g of sodium hydroxide and 4.68 g of deionized water were stirred and mixed to obtain a mixed solution;
[0097] 2) After adding 0.5 g of aluminum hydroxide to the mixed solution, the mixture was stirred vigorously for 10 minutes; then 40 g of silicon source (containing 30 wt.% SiO2) and 0.36 g of seed crystals were added, and the mixture was stirred vigorously for 2 h to obtain a mixed gel;
[0098] 3) The mixed gel was transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for dynamic crystallization at a crystallization temperature of 160°C for 12 hours. After the crystallization, the kettle was taken out and quenched to room temperature with water, centrifuged and washed with water until neutral. The obtained sample was dried in an oven at 120°C and then calcined in a muffle furnace at a high temperature of 550°C for 10 hours to obtain Na-SSZ-13 zeolite;
[0099] 4) The calcined sample was ion exchanged three times in 1M NH4Cl solution, the amount of NH4Cl solution was: every 50mL NH4Cl solution corresponds to 1g zeolite, the ion exchange temperature was 70°C, the ion exchange time was 2h, and the SSZ-13 zeolite catalyst was obtained after high-temperature calcination again, which was named SSZ-13-8R.
[0100] Wherein, based on TMAdaOH, Urea, Na2O, Al2O3, SiO2, and H2O, the molar ratio of trimethylammonium adamantanum, urea, sodium hydroxide, aluminum source, silicon source, and deionized water is 14:8:7.5:1.6:100:1400.
[0101] Example 5
[0102] The preparation of the SSZ-13 zeolite catalyst of the present embodiment comprises the following steps:
[0103] 1) 1.21 g of urea, 23.64 g of a 25 wt.% TMAdaOH solution, 1.2 g of sodium hydroxide and 4.68 g of deionized water were stirred and mixed to obtain a mixed solution;
[0104] 2) After adding 0.5 g of aluminum hydroxide to the mixed solution, the mixture was stirred vigorously for 10 minutes; then 40 g of silicon source (containing 30 wt.% SiO2) and 0.36 g of seed crystals were added, and the mixture was stirred vigorously for 2 h to obtain a mixed gel;
[0105] 3) The mixed gel was transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for dynamic crystallization at a crystallization temperature of 160°C for 12 hours. After the crystallization, the kettle was taken out and quenched to room temperature with water, centrifuged and washed with water until neutral. The obtained sample was dried in an oven at 120°C and then calcined in a muffle furnace at a high temperature of 550°C for 10 hours to obtain Na-SSZ-13 zeolite;
[0106] 4) The calcined sample was ion exchanged three times in 1M NH4Cl solution, the amount of NH4Cl solution was: every 50mL NH4Cl solution corresponds to 1g zeolite, the ion exchange temperature was 70°C, the ion exchange time was 2h, and the SSZ-13 zeolite catalyst was obtained after high-temperature calcination again, which was named SSZ-13-10R.
[0107] Wherein, based on TMAdaOH, Urea, Na2O, Al2O3, SiO2, and H2O, the molar ratio of trimethylammonium adamantanum, urea, sodium hydroxide, aluminum source, silicon source, and deionized water is 14:10:7.5:1.6:100:1400.
[0108] Example 6
[0109] The preparation of the SSZ-13 zeolite catalyst of the present embodiment comprises the following steps:
[0110] 1) 0.73 g of urea, 13.5 g of a 25 wt.% TMAdaOH solution, 1.9 g of sodium hydroxide and 12.27 g of deionized water were stirred and mixed to obtain a mixed solution;
[0111] 2) After adding 0.5 g of aluminum hydroxide to the mixed solution, the mixture was stirred vigorously for 10 minutes; then 40 g of silicon source (containing 30 wt.% SiO2) and 0.36 g of seed crystals were added, and the mixture was stirred vigorously for 2 h to obtain a mixed gel;
[0112] 3) The mixed gel was transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for dynamic crystallization at a crystallization temperature of 160°C for 24 hours. After the crystallization, the kettle was taken out and quenched to room temperature with water, centrifuged and washed with water until neutral. The obtained sample was dried in an oven at 120°C and then calcined in a muffle furnace at a high temperature of 550°C for 10 hours to obtain Na-SSZ-13 zeolite;
[0113] 4) The calcined sample was ion exchanged three times in 1M NH4Cl solution, the amount of NH4Cl solution was: every 50mL NH4Cl solution corresponds to 1g zeolite, the ion exchange temperature was 70°C, the ion exchange time was 2h, and the SSZ-13 zeolite catalyst was obtained after high-temperature calcination again, which was named SSZ-13-6R-8T-12Na2O.
[0114] Wherein, based on TMAdaOH, Urea, Na2O, Al2O3, SiO2, and H2O, the molar ratio of trimethylammonium adamantanium, urea, sodium hydroxide, aluminum source, silicon source, and deionized water is 8:6:12:1.6:100:1400.
[0115] Comparative Example 1
[0116] This comparative example provides a method for preparing a conventional SSZ-13 zeolite catalyst, comprising the following steps:
[0117] 1) 23.64 g of 25 wt.% TMAdaOH solution, 1.2 g of sodium hydroxide and 4.68 g of deionized water were stirred and mixed to obtain a mixed solution;
[0118] 2) After adding 0.5 g of aluminum hydroxide to the mixed solution, the mixture was stirred vigorously for 10 minutes; then 40 g of silicon source (containing 30 wt.% SiO2) and 0.36 g of seed crystals were added, and the mixture was stirred vigorously for 2 h to obtain a mixed gel;
[0119] 3) The mixed gel was transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for dynamic crystallization at a crystallization temperature of 160°C for 12 hours. After the crystallization, the kettle was taken out and quenched to room temperature with water, centrifuged and washed with water until neutral. The obtained sample was dried in an oven at 120°C and then calcined in a muffle furnace at a high temperature of 550°C for 10 hours to obtain Na-SSZ-13 zeolite;
[0120] 4) The calcined sample was ion exchanged three times in 1M NH4Cl solution, the amount of NH4Cl solution was: every 50mL NH4Cl solution corresponds to 1g zeolite, the ion exchange temperature was 70°C, the ion exchange time was 2h, and the SSZ-13 zeolite catalyst was obtained after high-temperature calcination again, which was named SSZ-13-Ref.
[0121] Among them, the molar ratio of trimethylammonium adamantanum, sodium hydroxide, aluminum source, silicon source and water is 14:7.5:1.6:100:1400 based on TMAdaOH, Na2O, Al2O3, SiO2 and H2O.
[0122] Comparative Example 2
[0123] This comparative example provides a method for preparing a SSZ-13 zeolite catalyst using diethylamine as an additive, comprising the following steps:
[0124] 1) 0.88 g of diethylamine (DEA), 23.64 g of 25 wt.% TMAdaOH solution, 1.2 g of sodium hydroxide and 4.68 g of deionized water were stirred and mixed to obtain a mixed solution;
[0125] 2) After adding 0.5 g of aluminum hydroxide to the mixed solution, the mixture was stirred vigorously for 10 minutes; then 40 g of silicon source (containing 30 wt.% SiO2) and 0.36 g of seed crystals were added, and the mixture was stirred vigorously for 2 h to obtain a mixed gel;
[0126] 3) The mixed gel was transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for dynamic crystallization at a crystallization temperature of 160°C for 4 hours. After the crystallization, the kettle was taken out and quenched to room temperature with water, centrifuged and washed with water until neutral. The obtained sample was dried in an oven at 120°C and then calcined in a muffle furnace at a high temperature of 550°C for 10 hours to obtain Na-SSZ-13 zeolite;
[0127] 4) The calcined sample was ion exchanged three times in 1M NH4Cl solution, the amount of NH4Cl solution was: every 50mL NH4Cl solution corresponds to 1g zeolite, the ion exchange temperature was 70°C, the ion exchange time was 2h, and the SSZ-13 zeolite catalyst was obtained after high-temperature calcination again, which was named SSZ-13-6DEA.
[0128] Wherein, based on TMAdaOH, DEA, Na2O, Al2O3, SiO2, and H2O, the molar ratio of trimethylammonium adamantanum, diethylamine, sodium hydroxide, aluminum source, silicon source, and deionized water is 14:6:7.5:1.6:100:1400.
[0129] Comparative Example 3
[0130] This comparative example provides a method for preparing a SSZ-13 zeolite catalyst using dipropylamine as an additive, comprising the following steps:
[0131] 1) 1.21 g of dipropylamine (DPA), 23.64 g of a 25 wt.% TMAdaOH solution, 1.2 g of sodium hydroxide and 4.68 g of deionized water were stirred and mixed to obtain a mixed solution;
[0132] 2) After adding 0.5 g of aluminum hydroxide to the mixed solution, the mixture was stirred vigorously for 10 minutes; then 40 g of silicon source (containing 30 wt.% SiO2) and 0.36 g of seed crystals were added, and the mixture was stirred vigorously for 2 h to obtain a mixed gel;
[0133] 3) The mixed gel was transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene for dynamic crystallization at a crystallization temperature of 160°C for 4 hours. After the crystallization, the kettle was taken out and quenched to room temperature with water, centrifuged and washed with water until neutral. The obtained sample was dried in an oven at 120°C and then calcined in a muffle furnace at a high temperature of 550°C for 10 hours to obtain Na-SSZ-13 zeolite;
[0134] 4) The calcined sample was ion exchanged three times in 1M NH4Cl solution, the amount of NH4Cl solution was: every 50mL NH4Cl solution corresponds to 1g zeolite, the ion exchange temperature was 70°C, the ion exchange time was 2h, and the SSZ-13 zeolite catalyst was obtained after high-temperature calcination again, which was named SSZ-13-6DPA.
[0135] Among them, based on TMAdaOH, DPA, Na2O, Al2O3, SiO2, and H2O, the molar ratio of trimethylammonium adamantane, dipropylamine, sodium hydroxide, aluminum source, silicon source, and deionized water is 14:6:7.5:1.6:100:1400.
[0136] Test Example 1
[0137] The BET (specific surface area), V total (total pore volume), V micro (micropore volume), V meso (mesopore volume), the results are shown in Table 1 and Figure 4 .
[0138] Detection by XRF (X-ray fluorescence spectroscopy) a Silicon to aluminum ratio, the results are shown in Table 1.
[0139] Table 1
[0140]
[0141] According to Table 1, the specific surface area and pore structure of the SSZ-13 zeolite catalyst in Examples 1-4 and 6 are basically consistent with the SSZ-13-Ref zeolite catalyst in Comparative Example 1, indicating that adding urea or reducing the amount of trimethyladamantanamine will not affect the synthesis of the SSZ-13 zeolite catalyst. The SSZ-13 zeolite catalyst prepared in Example 5 has a lower specific surface area and a changed pore structure compared to Examples 1-4, indicating that an increase in the molar percentage of urea to silica will delay the crystallization of the SSZ-13 zeolite catalyst.
[0142] Test Example 2
[0143] The yield of the SSZ-13 zeolite catalyst is calculated by dividing the mass of the SSZ-13 zeolite catalyst by the mass of silica and alumina.
[0144] Figure 1 It is the SSZ-13 zeolite catalyst yield curve of Comparative Example 1 and Examples 1-5.
[0145] according to Figure 1It can be seen that with the increase of urea addition, the yield of SSZ-13 zeolite catalyst first increases and then decreases. When the molar percentage of urea to silica is 6 and 8, the yield of SSZ-13 zeolite catalyst is as high as 97.1% and 97.2%. Therefore, the molar percentage of urea to silica is preferably 6-8.
[0146] Test Example 3
[0147] The crystal size and morphology of the SSZ-13 zeolite catalyst were characterized by SEM images.
[0148] Figure 2a , Figure 2b , Figure 2c , Figure 2d , Figure 2e , Figure 2f , Figure 2g , Figure 2h , Figure 2i It is the SEM picture of comparative example 1-3 and embodiment 1-6 when the scale is 2 μm. Figure 2a1 , Figure 2b1 , Figure 2c1 , Figure 2d1 , Figure 2e1 , Figure 2f1 , Figure 2g1 , Figure 2h1 , Figure 2i1 These are SEM images of Comparative Examples 1-3 and Examples 1-6 when the scale is 1 μm.
[0149] As shown in the figure, the SSZ-13 zeolite catalysts prepared in Comparative Examples 1-3, Examples 1-4 and Example 6 all have a cube structure with sharp edges and corners. The diethylamine and dipropylamine added in Comparative Examples 2 and 3 are only crystallized for 4 hours to obtain SSZ-13 zeolite catalyst grains with complete and uniform morphology. In the embodiments of the present invention, the addition of urea requires 12-36 hours to completely crystallize, and as the amount of urea added increases, the morphology of the SSZ-13 zeolite catalyst changes. When the amount of urea added accounts for 10% of the molar amount of silica, the complete cubic crystal size of the SSZ-13 zeolite decreases and an amorphous morphology appears, indicating that urea will delay crystallization, reduce the particle size, and be beneficial to molecular diffusion, which is beneficial to catalytic performance; however, when the urea content increases, it will hinder crystallization, thereby reducing the crystallinity, which is not conducive to catalytic performance.
[0150] Test Example 4
[0151] The crystallization of SSZ-13 zeolite catalyst was characterized by XRD spectrum.
[0152] Figure 3 It is the XRD spectra of the SSZ-13 zeolite catalysts prepared in Comparative Examples 1-3 and Examples 1-6.
[0153] according to Figure 3 It can be seen that the SSZ-13 zeolite catalysts prepared in Comparative Examples 1-3 and Examples 1-6 all have a CHA topological structure, a strong XRD spectrum peak intensity, no impurity crystals, and a high degree of crystallinity. Therefore, the SSZ-13 zeolite catalysts prepared in the examples of the present invention all have relatively excellent catalytic performance.
[0154] Test Example 5
[0155] The effect of SSZ-13 zeolite catalyst on methanol to olefin reaction was evaluated by using a fixed bed microreactor-gas chromatography device, and the process was as follows: the SSZ-13 zeolite catalyst was pressed into tablets using a mold, crushed and screened to obtain catalyst particles with a particle size of 40-60 mesh, and 0.5 g was loaded into a fixed bed reaction tube, and methanol was fed using a double plunger micro-feed pump. The methanol-carrying gas was nitrogen, and the nitrogen and raw material methanol water mixture passed through the catalyst fixed bed from top to bottom. The reaction product was detected by a gas chromatograph (FID detector). Before the reaction, the catalyst needs to be pretreated, and the reactor temperature is raised from room temperature to the reaction temperature of 350°C for 1 hour and maintained for 1 hour. The reaction conditions are: the mass space velocity is 1h -1 , reaction temperature 350℃, pressure 1.07×10 5 Pa.
[0156] At the beginning of the reaction, the methanol conversion rate was 100%, and the reaction time when the methanol conversion rate dropped to 98% was taken as the catalyst life. Figure 5 The relationship between reaction time and methanol conversion rate when the SSZ-13 zeolite catalyst prepared in Comparative Example 1, Example 3 and Example 6 is used for methanol to olefins.
[0157] The olefin selectivity is calculated based on the ratio of the production of dienes (ethylene and propylene) in the methanol conversion product to the amount of all products in that period of time. Figure 6 The olefin selectivity results when the SSZ-13 zeolite catalysts prepared in Comparative Example 1, Example 3, and Example 6 are used in methanol to olefins.
[0158] Combination Figure 5 and Figure 6 It can be seen that the life of the SSZ-13 zeolite catalyst prepared in Comparative Example 1 is 3 hours, and when the SSZ-13 zeolite catalyst prepared in the present invention is used for methanol to olefins, the catalyst life is 3-16 hours, which shows that the SSZ-13 zeolite catalyst of the present invention has excellent anti-deactivation performance. In addition, when the molar percentage of urea to silicon dioxide is 6, the diene selectivity can reach up to 88%, which has good catalytic performance.
[0159] In order to make the purpose, technical solution and advantages of the present invention clearer, the above-mentioned technical solution of the present invention is clearly and completely described in combination with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, but not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a SSZ-13 zeolite catalyst, characterized in that: The following steps are included: 1) mixing a template, sodium hydroxide and deionized water to obtain a mixed solution; 2) adding an aluminum source to the mixed solution, and then adding a silicon source and a seed crystal to obtain a mixed gel; 3) performing crystallization treatment and post-treatment on the mixed gel in sequence to obtain Na-SSZ-13 zeolite; 4) sequentially subjecting the Na-SSZ-13 zeolite to ion exchange, drying, and calcination to obtain the SSZ-13 zeolite catalyst; Wherein, the template agent includes trimethylammonium adamantane and urea; Calculated on the basis of TMAdaOH, Urea, Na2O, Al2O3, SiO2 and H2O, the molar ratio of trimethylammonium adamantanum, urea, sodium hydroxide, aluminum source, silicon source and deionized water is (1-14): (1-10): (5-15): (0.5-5): (50-100): (500-4000).
2. The method for preparing the SSZ-13 zeolite catalyst according to claim 1, characterized in that: The molar ratio of trimethylammonium adamantanum, urea, sodium hydroxide, aluminum source, silicon source and deionized water is (1-14): (2-8): (6-15): (0.5-2.5): (60-100): (1000-2000).
3. The method for preparing the SSZ-13 zeolite catalyst according to claim 1, characterized in that: The molar ratio of trimethylammonium adamantane, urea, sodium hydroxide, aluminum source, silicon source and deionized water is (5-14): (6-8): (6-13): (1-2.5): (80-100): (1200-1500).
4. The method for preparing the SSZ-13 zeolite catalyst according to any one of claims 1 to 3, characterized in that: The aluminum source includes aluminum hydroxide; the silicon source includes alkaline silica sol.
5. The method for preparing the SSZ-13 zeolite catalyst according to any one of claims 1 to 3, characterized in that: The temperature of the crystallization treatment is 140-180° C. and the time is 12-36 hours.
6. The method for preparing the SSZ-13 zeolite catalyst according to any one of claims 1 to 3, characterized in that: The ion exchange solution is a 1M NH4Cl solution, and the ion exchange is performed on 1g of the Na-SSZ-13 zeolite with every 50mL of the NH4Cl solution.
7. The method for preparing the SSZ-13 zeolite catalyst according to claim 6, characterized in that: The ion exchange is performed three times, each time for 1-3 hours.
8. The method for preparing the SSZ-13 zeolite catalyst according to any one of claims 1 to 3 and 7, characterized in that: The temperature of the ion exchange is 60-80°C.
9. A SSZ-13 zeolite catalyst, characterized in that The SSZ-13 zeolite catalyst is prepared by the method according to any one of claims 1 to 8, wherein the silicon-aluminum ratio of the SSZ-13 zeolite catalyst is 10-100, and the micropore volume is 0.15-0.35 cm 3 / g, specific surface area is 300-700m 2 / g, and the average grain size is 100nm-1μm.
10. A method for preparing olefins from methanol, characterized in that: The SSZ-13 zeolite catalyst according to claim 9 is used.
Citation Information
Patent Citations
Methanol-to-olefin catalyst and preparation method thereof
CN106925340A
Methanol-to-olefin catalyst and preparation method thereof
CN109201109A